202k views
2 votes
f(x) = 2x + 4 and g(x) = -8f(x). = What equation shows the correct rule for the function g? O g(x) = -4x O g(x) = -4x + 4 = g(x) = -8x - 32 O g(x) = -4x - 32 – -

f(x) = 2x + 4 and g(x) = -8f(x). = What equation shows the correct rule for the function-example-1

1 Answer

2 votes

The given functions are


\begin{gathered} f(x)=(1)/(2)x+4 \\ g(x)=-8f(x) \end{gathered}

Multiply f by -8 to get g


\begin{gathered} g(x)=-8((1)/(2)x+4) \\ g(x)=-8((1)/(2)x)+(-8)(4) \\ g(x)=-4x+(-32) \\ g(x)=-4x-32 \end{gathered}

The correct answer is D

User Hopey One
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.